Educational training in Physical Education in the context of current technological virtuality - Bennasar, Miguel (2022)
The study's primary purpose focused on analyzing educational training in Physical Education and the use of technological tools in the current context as a way of perceiving the reality of the use of technological platforms in academic exchanges in a virtual way. The research is methodologically attached to descriptive field studies. The data collection instrument was the survey, made up of 12 items, with their alternatives, which allowed the informants to extract the information from which the analyzes were based. For validity, expert judgment was applied, and reliability was determined using the Cronbach Coefficient, whose result was 0.89. As conclusions, the students stated that ICTs represent a significant fact for understanding educational realities. Likewise, they showed disagreement about Physical Education being versatile under the virtual modality.